PENGARUH INDEPENDENSI, CROSS-MEMBERSHIP, DAN FREKUENSI RAPAT DEWAN PENGAWAS SYARIAH TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Bank Umum Syariah yang Terdaftar di BI Tahun 2014-2020) - Sifa Hayu Ramadhani; Adityawarman1 Adityawarman1 (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of independence, cross-membership, meetings frequency of Shariah Supervisory Board (SSB) and firm performance of Islamic Banks in Indonesia. Firm performance was measured by return on asset (ROA). This study uses the independent variables independence, cross-membership, and meetings frequency of SSB. The sample uses in this study is Islamic Bank listed on the Bank Indonesia during the period 2014-2020. The number of samples is 12 companies taken by purposive sample method. Analytical method of the study was linear regression, which previously passes the classic assumption test. The results indicates that the independence, cross-membership and meetings frequency of SSB has significant positive effect on ROA